Initial cassh flow valuation for startup entrerprises - Carpio Mendoza, José Julio; León Castro, Ernesto; Urciaga García, José I. (2021)
Most of developing countries have a heavy dependency in micro, small and medium (MSMEs) enterprises in order to have economic growth, house hold income and social stability (Spring & McDade, 1998; Chu et al., 2007).